MEDIASI CUSTOMER SATISFACTION DAN INTELLECTUAL CAPITALATAS PENGARUH DIGITAL MARKETING TERHADAP KINERJA PERUSAHAAN - Yuliati Yuliati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
The aim of this study is to provide clarity of intellectual capital effects and customer satisfaction as a mediating variable in the relationship between digital marketing for firm performance. The study was conducted on Small Medium Enterprises (SMEs) in Kudus district by taking a sample of 134 SME managers such as owners and operational managers. Through structural equation modeling (SEM) analysis, it is discussed that the mediated hypothesized effect is statistically significant. In other words, intellectual capital and customer satisfaction can bridge the relationship of digital marketing variables to firm performance. This finding helps management in understanding the ability of internal resources to be able to utilize information technology to support the resources they have. Therefore, SMEs must pay attention to factors both internal and external, agreeing to understand the suitability of the firms in determining the most appropriate use of digital marketing.